2013
DOI: 10.1590/0102-311x00084712
|View full text |Cite
|
Sign up to set email alerts
|

Ingestão de folato nos períodos pré e pós-fortificação mandatória: estudo de base populacional em São Paulo, Brasil

Abstract: Analisou-se a ingestão de folato nos períodos pré e pós-fortificação. Os dados dietéticos foram coletados por recordatório de 24 horas (R24h) no Inquérito de Saúde de São Paulo (ISA-Capital) em 2003 e 2007/2008, estratificando-se a população segundo fase da vida e sexo. Utilizaram-se os valores de recomendação: necessidade média estimada (EAR) e nível máximo de ingestão tolerada (UL) e o método "EAR como ponto de corte" para estimar a inadequação da ingestão. Houve redução na prevalência de inadequação da inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
(50 reference statements)
3
9
0
Order By: Relevance
“…The prevalence of inadequate folate intake has dropped since the adoption of the mandatory fortification of flour with folic acid in Brazil [29], but, at the same time, the load of methionine in this population is supposed to be high, due to the high intake of meat [30] and beans [31]. In this situation, homocysteinemia may arise from impaired methionine metabolism, and, consequently, more folate, B12 and betaine are needed to remethylation Hcy back to methionine [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of inadequate folate intake has dropped since the adoption of the mandatory fortification of flour with folic acid in Brazil [29], but, at the same time, the load of methionine in this population is supposed to be high, due to the high intake of meat [30] and beans [31]. In this situation, homocysteinemia may arise from impaired methionine metabolism, and, consequently, more folate, B12 and betaine are needed to remethylation Hcy back to methionine [3].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the transmethylation demand due to the methionine load, and the high intake of folic acid from mandatory fortification and adequate status of other B vitamins [29], [30], [31], the possible mechanism underlying the reduction effects of FV intake below the 75 th percentile could be that the homocysteine metabolism is working well, but, above this level, folate acts indirectly to lower homocysteine levels and insures optimal functioning of the remethylation pathway. However, it is known that high oral doses of folic acid can bypass the normal folate absorption mechanism [36].…”
Section: Discussionmentioning
confidence: 99%
“…Another Brazilian study with adolescents, adults, and older adults found that breads and beans contribute most to dietary folate, and breads provided the highest contribution regardless of the subject's age 16 . The established folate requirement of pregnant women exceeds that of nonpregnant women, and it is challenging to meet the requirement without fortified foods and/or supplementation 30 .…”
Section: Discussionmentioning
confidence: 98%
“…The results of a previous study showed that homozygotes (TT) for the MTHFR 677C>T mutation presented one-third of the expected activity for this enzyme [31]. It has been suggested that folic acid from fortified food primarily increases the intake and serum concentration of folate [32]. The synthetic form of folate, folic acid, needs to be converted into 5-methyltetrahydrofolate (5MeTHF) through the enzyme MTHFR.…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid fortification considerably reduces the inadequacy of folate prevalence within levels considered to be safe in the inhabitant population of São Paulo [32]; however, the profile of genetic variability among this population remains unknown. Indeed, the presence of these polymorphisms modifies the metabolism and alters the concentrations of these metabolites, as differences in homocysteine concentrations were observed in individuals with genetic variants of MTHFR 677C>T. These effects in health and disease are inconclusive; therefore, the evaluation of such variants must be considered in future epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%